Diagnoses of Ovine Infection by the Serotype-4 Bluetongue Virus on Minas Gerais, Brazil - Lima, Pamela Aparecida; Utiumi, Kiyoko Uemura; Nakagaki, Karen Yumi Ribeiro; Biihrer, Daniel Arrais; Albuquerque, Adriana Silva; Souza, Fernanda Rezende; Matos, Ana Carolina Diniz; Lobato, Zélia Inês Portela; Drimeier, David; Peconick, Ana Paula; Varaschin, Mary Suzan; Raymundo, Djeison Lutier (Acta Scientiae Veterinariae, 2016)
Background: Bluetongue (BT) is a viral disease transmitted by hematophagous vectors of the genus Culicoides. In Brazil, the identifcation of antibodies against the virus has been held for over thirty years, however clinicopathological diagnosis of the disease are scarce. The frst reported case occurred in the state of Paraná in 2001, confrmed by isolation and identifcation of serotype 12 of BTV. In the state of Rio Grande do Sul, in 2009, two outbreaks confrmed and was identifed the serotype 12. Serotype 4 was isolated during an outbreak in the state of Rio de Janeiro in 2013. This study describes the Diagnoses of ovine infection by the serotype-4 bluetongue virus in Minas Gerais, Brazil. Case: In a farm in the Southern region of the state of Minas Gerais, a group of 28 male sheep, was sent for necropsy at the Setor de Patologia Veterinária of Universidade Federal de Lavras (SPV-UFLA). In a ﬂock of 80 male sheep 28 died with clinical signs of respiratory distress, whereas other showed signs of anemia and hypoproteinemia, cough, sneezing, prostration, fever, mucopurulent nasal discharge, anemia and submandibular edema. At necropsy, the main changes observed were cranioventral pulmonary consolidation, hemorrhage at the base of the pulmonary artery and ulcerating lesions in the hard palate mucosa, rumen and reticulum. The histological changes consisted of bacterial bronchopneumonia, papillary necrosis associated with bacterial structures, multifocal vasculitis in the submucosa and thrombi in blood vessels of the serosa in the rumen and reticulum, hyaline and ﬂocculate necrosis in esophageal muscle, skeletal and cardiac muscle fbers were also observed, associated with moderate mononuclear inﬂammatory infltrate between fbers and around blood vessels. Discussion: The diagnosis of BT was confrmed by the identifcation of nucleic acids of the virus in blood samples and from tissues of animals from the herd by RT-PCR and by the detection of antibodies against Bluetongue virus with the agar gel immunodiffusion (AGID) test using serum samples from the remaining herd animals. Serotype 4 was identifed in three of the samples inoculated into KC cells. The hemorrhage at the base of the pulmonary artery, one characteristic fndings, was found in three of the necropsied sheep. The pulmonary lesions observed in the present study strongly suggest the occurrence of pneumonia caused by opportunistic bacteria, especially Mannheimia haemolytica, which is commonly associated with pneumonia in sheep infected with BTV. This work is the frst in the state of Minas Gerais and the fourth in Brazil to report an outbreak of the disease with clinical signs. The economic impact of bluetongue results not only from the direct losses of animals to the disease, but also to the correlation among BTV infection and other problems including pneumonia, abortion and verminoses. In a study focused on the characteristics of ovine farming in Minas Gerais, farmers from the center-southwest reported that abortion and pneumonia were among their main problems. Thus, further epidemiological studies on BTV may improve the level of identifcation of infected herds and may help promote prophylactic measures. Necropsies and histopathology exams constitute crucial tools for diagnosis, because most cases present at a sub-clinical stage or in association with other, concomitant diseases. Keywords: BTV 4, viral diseases, sheep, RT-PCR e IDGA